2002
DOI: 10.1007/bf03345101
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral mass is associated with interleukin 1 receptor autoantigen and TNF-α gene polymorphisms in post-menopausal Mediterranean women

Abstract: Bone mass is known to be under genetic control. Interleukin-1 (IL-1), interleukin-6 (IL-6) and TNF-alpha are strong inductors of bone resorption. The estrogenic deficiency that occurs during menopause leads to an increase in the production of these cytokines. We analyzed the genetic susceptibility of several polymorphisms of the interleukin-1 receptor antagonist (IL-1ra), IL-6 and TNF-alpha genes in lumbar spine and hip bone mass in a sample of post-menopausal Caucasian Mediterranean women with osteoporosis. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
22
2
Order By: Relevance
“…Allelic variations of IL1ra gene have been correlated to bone loss rate at lumbar spine. The A2 allele was associated to a greater lumbar or hip BMD and a bone loss protective effect in comparison to noncarriage of the allele in postmenopausal women [112,113]. The alleles A1 and A3, however, were significantly more frequent in osteoporotic patients compared with age-matched normal controls, with a significant relative risk of osteoporotic fractures of 1.68 (95% CI, 1.01-2.77) [114].…”
Section: Effects Of Anti-cytokine Biologic Therapies On Bonementioning
confidence: 89%
“…Allelic variations of IL1ra gene have been correlated to bone loss rate at lumbar spine. The A2 allele was associated to a greater lumbar or hip BMD and a bone loss protective effect in comparison to noncarriage of the allele in postmenopausal women [112,113]. The alleles A1 and A3, however, were significantly more frequent in osteoporotic patients compared with age-matched normal controls, with a significant relative risk of osteoporotic fractures of 1.68 (95% CI, 1.01-2.77) [114].…”
Section: Effects Of Anti-cytokine Biologic Therapies On Bonementioning
confidence: 89%
“…Nor does the polymorphism influence the peak bone mass although another polymorphism located in the promoter region of the gene, -863 CA [19] , does. Only Fontova et al [23] , in a study on 104 postmenopausal women with osteoporosis and 51 without, found a higher bone mass in a group of patients with nonsevere osteoporosis and the G allele.…”
Section: Discussionmentioning
confidence: 99%
“…The significant associations at the femoral neck, total hip, and distal radius were mostly decided by a single study (Moffett et al, 2004) that contributed more than All studies recruited European populations at whole body and distal radius; all subjects were women at the total hip, distal radius, middle radius, and ultradistal radius; all studies were classified as high quality at the trochanter, whole body, Ward's triangle, distal radius, middle radius, and ultradistal radius. Only the difference for CC/CG versus GG was included in one study (Fontova et al, 2002 Only the difference for CC versus CG/GG was included in one study (Ferrari et al, 2003). (2004) Ferrari (2001) Moffett (2004) Lorentzon ( For each study, the estimate of mean BMD difference and its 95% CI is plotted with a diamond (A) and a horizontal line.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one duplicated study (Ferrari et al, 2003) and one study with a problematic BMD at the Ward's triangle (Ferrari et al, 2004) from two articles were further excluded. Therefore, 23 studies with 11,957 subjects from 16 articles were eligible in the BMD analysis (Lorentzon et al, 2000;Ferrari et al, 2001;Ota et al, 2001;Fontova et al, 2002;Garnero et al, 2002;Chung et al, 2003;Ferrari et al, 2003;Yamada et al, 2003;Ferrari et al, 2004;James et al, 2004;Moffett et al, 2004 C, cohort; CS, cross-sectional study; CC, case-control study; CRT, cross-sectional on randomized control trial; FN, femoral neck; LS, lumbar spine; WB, whole body; TH, total hip; TR, trochanter; 1/3R, one-third distal radius; MID, mid-distal radius; UDR, ultradistal radius; WT, Ward's triangle; DR, distal radius; PR, proximal radius; NA, not available; SD, standard deviation; BMI, body mass index. All population-based studies at all skeletal sites analyzed; all studies recruited Asian populations at the lumbar spine and whole body; all Asian studies recruited Japanese populations at the trochanter and Ward's triangle; all studies were classified as high quality at the trochanter and Ward's triangle.…”
Section: Eligible Studiesmentioning
confidence: 99%